The study of magnetic field pattern and induction motors performance during sinusoidal and harmonics condition / Mohamad Zulkifli Mohd Salim - Mohd Salim, Mohamad Zulkifli (2013)
This research deals with an analysis of magnetic field pattern in three phase stator machines during sinusoidal and harmonic condition. Harmonics component will determine the pattern of rotating magnetic field generate by machines. To evaluate the harmonic components, this paper proposes a new harmonics analysis method that considers the pattern of net rotating magnetic flux density in three phase stator. With this method, the harmonics component can be determined by analyze the pattern of magnetic field instead by frequencies, currents and voltages. In this analysis, only stator magnetic field is created. Rotating magnetic field and harmonics also have become a main concern related to motor performances. Further, finite element method (FEM) used to analyze effect of space and time harmonics to induction motors performance. Both space harmonics and time harmonic equivalent circuits are presented. These methods were powerful tools to analyze motor parameters such as harmonics current and torques. Harmonics slips and torques formulas are derived and torques versus speed graph for both types of harmonic are generated and analyzed. This analysis will be compare to the pattern magnetic field generated from previous analysis so further performance of motor can be determined by looking to the pattern of magnetic field.